2006
DOI: 10.1177/08830738060210040301
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Outcome of Severe Neonatal Nonhemolytic Hyperbilirubinemia

Abstract: We studied the effects of hyperbilirubinemia on brainstem auditory pathways and neurodevelopmental status in 99 full-term neonates with severe nonhemolytic hyperbilirubinemia (total serum bilirubin level = 301 to 500 micromol/L) born between 1995 and 2000. These were divided into three groups: group 1, moderate hyperbilirubinemia (n = 30; mean maximum total serum bilirubin = 320.7 micromol/L or 18.9 mg%); group 2, severe hyperbilirubinemia (n = 63; mean maximum total serum bilirubin = 369.0 micromol/L or 21.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 45 publications
3
42
0
1
Order By: Relevance
“…Similar cases had already been reported [18,19]. High levels of unconjugated bilirubin have been associated with neuron damage, and the auditory brainstem nuclei and inferior colliculi are often the first to be involved, with consequent hearing abnormalities [20].…”
Section: Discussionsupporting
confidence: 55%
“…Similar cases had already been reported [18,19]. High levels of unconjugated bilirubin have been associated with neuron damage, and the auditory brainstem nuclei and inferior colliculi are often the first to be involved, with consequent hearing abnormalities [20].…”
Section: Discussionsupporting
confidence: 55%
“…However, an unusually extended period of ABR recovery has been suggested by other researchers. Wong et al [8] found that most abnormal ABR returned to normal at 2 years in a group of term babies suVering from severe hyperbilirubinemia. Kitagawa et al [19] reported ABR and behavioral hearing tests recovery in children with congenital CNS anomalies, which in some cases took several years to occur.…”
Section: Abr Reversibilitymentioning
confidence: 98%
“…Despite this widely accepted rule, transient ABR abnormalities and reversible sensorineural hearing losses have been sporadically reported. SigniWcant improvement or complete recovery of ABR thresholds in HR neonates treated for hyperbilirubinemia is probably the most characteristic example of ABR reversibility [7,8]. Complete or partial restoration of ABR has been infrequently reported in HR infants [9] and pediatric patients suVering from a variety of medical conditions, such as hypoxia/ischemia [10], metabolic [11] and neurologic diseases [12,13], sudden idiopathic hearing loss [14] and meningitis [15].…”
Section: Abr Reversibilitymentioning
confidence: 99%
“…Similar decrease in prevalence has been reported by Chen et al (10.42% in hemolytic group and 2% in non-hemolytic group were neurodevelopmentaly abnormal at initial evaluation and returned to normal on follow up at 3 years). (4) Yilmaz et al in 2001 reported neurodevelopmental abnormalities in 11.5% cases in their study using DDST. (5) This prevalence is quite similar to the prevalence of neurodevelopmental abnormalities in our study (10.42%).…”
Section: Discussionmentioning
confidence: 93%